Effect of cell temperatures and flow-field patterns of bipolar plate electrodes on the performance of proton exchange membrane fuel cell by computational simulation - Saraihom, Lirada; Srimongkon, Kridsanapan; Ruttanapun, Chesta; Tangtrakarn, Apishok; Faibut, Narit; Uppachai, Pikaned; Towannang, Madsakorn; Amornkitbamrung, Vittaya (My University, 2017)
The performances of fuel cell employing a bipolar plate with different gas-flow-field patterns for proton exchange membrane fuel cell (PEMFC) were simulated using higher-order polynomials (h-p) finite element method (h-p FEM). The patterns of each model were as follows: the straight pipe on both sides (Model 1), the serpentine flow-field for anode and the straight pipe for cathode (Model 2), the slotted serpentine for anode and the straight pipe for cathode (Model 3), and the serpentine on both sides (Model 4). It was found that as the cell temperature increased, the diffusion velocity of reactant gases and Maxwell-Stefan-diffusion coefficient of proton dramatically increased. The performance of PEMFC reached the highest value as the flow velocity of reactant gases and the diffusion coefficient of proton through membrane were optimized at the temperature of 80 °C. The most efficient flow-field pattern in this study is Model 2.
Keywords: Diffusion velocity of gas; Flow-field pattern; Mathematical modeling; PEM fuel cell